High-throughput sequencing of Potato virus M from tomato in Slovakia reveals a divergent variant of the virus - Miroslav Glasa; Katarína Šoltys; Lukáš Predajňa; Nina Sihelská; Jaroslav Budiš; Michaela Mrkvová; Ján Kraic; Daniel Mihálik; Ana Belén Ruiz-García (Plant Protection Science, 2019)
High-throughput sequencing (HTS) analysis of tomato (Solanum lycopersicum) samples revealed the presence of Potato virus M (PVM) in this crop in Slovakia. Full-length genomes of three PVM isolates were obtained using both HTS and Sanger sequencing validation. While two isolates (T40 and T50) were shown to belong to major Group I, a divergent T20 isolate was phylogenetically unrelated to any known PVM variant, potentially representing a new phylogenetic group. Despite a relatively high intraspecies diversity (17.3 ± 0.3%), no evidence of recombination was detected in the dataset of available complete PVM sequences. Conventional screening of tomato plants in Slovakia using ELISA and RT-PCR further confirmed a frequent occurrence of PVM in this host. Developed RT-PCR showed its polyvalence to detect the PVM Group I isolates, however, in silico analysis of primer binding sites indicated its compromised use for Group II isolates. Our results further pinpoint the significance of HTS for unbiased unveiling of virus diversity and a need for continual optimisation of molecular detection tools.